High pressure phase equilibria applications involving supercritical fluids - Suleiman, Norhidayah (2016)
This thesis describes the investigation of phase behaviour of binary and ternary mixtures at high pressure. The particular applications chosen to be explored in this phase behaviour investigation were supercritical fluid electrodeposition (SCFED) and carbon capture and storage (CCS). Chapter 1 introduces the phase behaviour of mixtures. Chapter 2 describes the equipment and analytical techniques used throughout this thesis including the high-pressure variable-volume view cell, electrical conductivity cell, high pressure FTIR cell, and high-pressure optical fiber phase analyser. Chapter 3 details the solubility and conductivity investigation of several supporting electrolytes in difluoromethane (CH2F2), which provided an electrochemical bath with sufficient conductivity for electrodeposition in supercritical fluids. The most effective supporting electrolyte amongst the eight ionic compounds tested was [N(nC4H9)4][Al(OC(CF3)3)4] which was found to give a moderate solubility and the highest conductivity (222 Scm2mol-1) in CH2F2. [N(nC4H9)4][Al(OC(CF3)3)4] was followed by [N(nC4H9)4][FAP] and [N(nCH3)4][FAP], , making all of them to be satisfactory potential supporting electrolytes for SCFED. Chapter 4 describes the investigation of water solubility in CO2/N2 mixtures relevant to the CCS process. The scope of the investigation covers a wide pressure range and two levels of N2 (xN2= 0.05 and xN2= 0.10). This experimental study was conducted by using the FTIR technique as described in further detail in Chapter 2. It was found that the presence of N2 in CO2 lowered the solubility of H2O in supercritical CO2 with N2 compared to pure CO2. The solubility of water also decreases significantly when the concentration of N2 is increased from 5% to 10%. Chapter 5 further explores the role of phase behaviour in the application of CCS with the investigation of the phase envelope of the ternary mixtures of CO2 and permanent gases (Ar, N2, and H2). Three ternary mixtures were measured (90% CO2 + 5% N2 + 5% Ar, 98% CO2 + 1% N2 + 1% Ar, and 95% CO2 + 3% H2 + 2% Ar) by using the fiber optic reflectometer, as described in further detail in Chapter 2. The experimental data presented in this part also have been used to validate the equation of state for the CCS applications. It was found that the phase envelope of CO2 shifted to a higher pressure and the two-phase region become broader with the presence of permanent gases. Overall, both GERG-2004 and gSAFT provide a good agreement between the predicted and experimental data for all the ternary mixtures investigated, with the exception of the bubble-point line for the 3%H2 + 2%Ar + 95% CO2 mixture. Finally, Chapter 6 summarises the research that was conducted in this thesis. It also evaluates the progress made towards achieving the aims initially set-up in Chapter1